Prolonged Breastfeeding Is Associated With Lower Risk Of Severe Hand, Foot And Mouth Disease In Chinese Children. Issue 3 (March 2016) - Li, Yaping; Deng, Huiling; Li, Mei; Wang, Wenjun; Jia, Xiaoli; Gao, Ning; Dang, Shuangsuo
Abstract : To assess whether breastfeeding duration can affect risk of severe hand, foot and mouth disease (HFMD) later in childhood, we retrospectively analyzed demographic, environmental and breastfeeding data on 603 children with severe HFMD and 1036 children with mild HFMD. Multivariate analysis showed that breastfeeding for 6–12 months significantly reduced the risk of severe HFMD, as did breastfeeding for >12 months. Abstract : Supplemental Digital Content is available in the text.